Making world hunger free by 2030 through agricultural research, education and extension - Singh, A. K.; Burman, R. Roy (Indian Farming, 2018)
Technically, hunger is the result of food deprivation. Right to food or right to freedom from hunger is an internationally recognized right. The commitment of nations to make the world free from hunger can also be gauged from the universally accepted Sustainable Development Goals. The SDG 2 made clear that by 2030 all forms of hunger and malnutrition must end. In accord of this direction, India, being an emerging global leader, has set its armor ready to achieve the target by 2030 but the task of achieving hunger free world by 2030 is tricky especially when India’s position on Global Hunger Index scrolled down to 100th position with more than 800 million are suffering from hunger, 8% of Indians do not get two square meals a day and there are pockets where severe under-nutrition takes its toll even today. India supports 18% of world population on 2.3% of geographical area indicating a highly dense habitation of its population. Every third child born is under weight and over 40 million stunted and 17 million children are wasted.